On Asymptotically Lacunary Statistical Equivalent Double Sequences of Fuzzy Numbers - Mongkolkeha, Chirasak; Thounthong, Phatiphat; Kumam, Poom (Communications in Mathematics and Applications, 2016)
In this paper, we present the asymptotically double lacunary statistical equivalent and strongly asymptotically double lacunary statistical equivalent which is a natural combination of the definition for asymptotically equivalence and lacunary statistical double sequences of fuzzy numbers. In addition, we also give some relations among these new notions.